Fixed-dose combination fluticasone/formoterol for asthma treatment in a real-world setting: meta-analysis of exacerbation rates and asthma control. Issue 1 (31st December 2023) - Papi, Alberto; Qasuri, Murtaza; Chung, Ernestine; Abdelbaset, Mohamed; Aly Moussa, Mohamed; Backer, Vibeke; Schmidt, Olaf; Usmani, Omar
ABSTRACT: Background: Treatment guidelines for asthma management are derived almost exclusively from the results of controlled clinical trials undertaken in carefully selected patient populations; meaning that their outcomes may not reflect the true performance of treatments when used in general daily medical practice. The aim of this meta-analysis was to combine the results of observational studies investigating the fluticasone propionate/formoterol (FP/FORM) fixed-dose combination in real-world asthma patients. Methods: A systemic literature review was completed in March 2019 using the PubMed database. We identified 394 studies. Five studies, which included a total of 4756 patients treated with FP/FORM, were judged eligible and included in the meta-analysis. Results: The estimated severe asthma exacerbation rate was 11.47% (95% CI, 5.8 to 18.72%), calculated from the random effect model. A sensitivity analysis excluding 2 studies (one was an outlier, and the exacerbation rate for the studied treatment alone could not be determined in the other) showed a 7.04% rate of severe asthma exacerbations. The estimated relative risk of the incidence of severe asthma exacerbations was 0.323 (95% CI, 0.159 to 0.658). The estimated asthma control rate was 60.6% (95% CI, 55.7% to 65.6%). The odds of achieving asthma control significantly increased by FP/FORM compared with pre-study conditions (estimated odds ratio: 2.214 [95% CI, 1.292 to 3.795]; p  < 0.001). Conclusions: The findings of this meta-analysis confirm the effectiveness of FP/FORM for the treatment of asthma patients in a real-world setting beyond the limitations of RCTs.